OUTBREAK OF CRYPTOSPORIDIOSIS IN SEA CAGED TURBOT (PSETTA MAXIMA) - FIORAVANTI MARIALETIZIA; CAFFARA MONICA; GUSTINELLI ANDREA; PALENZUELA OSWALDO; KRIZANAC SILVIA; ČOLAK SLAVICA; QUAGLIO, FRANCESCO (EAFP, 2015)
Turbot (Psetta maxima) is currently one of the most promising species for European mariculture but although most of the critical aspects threatening production have been optimized, transmissible diseases may still represent a limiting factor. In Autumn 2014 two batches of 5 turbot (mean weight 305 g) caged in northern Adriatic Sea and showing melanosis, exophthalmos and skin/fin lesions were subjected to bacteriological and parasitological examination. Visceral organs of twenty fish from the same two cages were fixed directly on the field in 10% buffered formalin. Necropsy showed in all specimens pale-yellow liver and intestinal distension with abundant mucous contents. From the fish owing to one batch ascites was also observed and bacteriological exam allowed to isolate Vibrio scophthalmi. Parasitological exam did not show presence of parasites in any organs except for intestine where developmental stages of not identifiable parasites were observed. In order to identify them, portions of intestine from all fish were subjected to DNA extraction followed by PCR of the 18S rDNA and sequencing. BLAST analysis of the sequences permitted to ascribe the parasites to the genus Cryptosporidium. At histology the presence of a mild-to-severe infection by cryptosporidia was detected in the intestine of all fish from both cages. Extracytoplasmic stages of parasites adhering to the luminal surface of the epithelial cells were observed, generally with the presence of intra-epithelial sporogonic stages located deeply within the enterocytes layer. In some areas, several oocysts were present within vacuolated areas in the mucosa, with diffuse necrosis, epithelial sloughing off and loss of the enterocytes brush border; lamina propria and submucosa were oedematous. Inflammatory response involving mainly lymphocytes and, in heavy infections, rodlet cells was noticed. In some fish also the stomach was affected. Severe pathological changes were mainly observed in presence of numerous intra-epithelial oocysts. The lesions here ...